Polyethylene microplastics disrupt renal function, mitochondrial bioenergetics, redox homeostasis, and histoarchitecture in Wistar rats - Kehinde, Samuel Abiodun; Olajide, Abosede Temitope; Ogunsanya, Sanmi Tunde; Fatokun, Tolulope Peter; Olulana, Deborah Itunuoluwa; Olabiyi, Folorunsho Adewale; Faokunla, Opeyemi; Tham, Chau Ling; Chusri, Sasitorn (Nature Research, 2025)
The pervasive environmental presence of polyethylene microplastics (PE-MPs) raises growing concerns about their potential systemic toxicity, particularly in renal physiology. This study investigated the nephrotoxic effects of PE-MPs, focusing on renal function, oxidative stress, mitochondrial integrity, and histopathological outcomes. Male Wistar rats were orally administered PE-MPs at 15 and 60 mg/kg body weight daily for 28 days. Renal function biomarkers, electrolyte levels, oxidative stress markers, mitochondrial enzyme activities, and histological changes were assessed using standard biochemical assays and H&E staining. PE-MPs exposure resulted in dose-dependent elevations in serum creatinine, BUN, uric acid, cystatin C, ACR, and KIM-1, indicating glomerular and tubular dysfunction. Oxidative stress was evidenced by depleted antioxidants (AA, GSH, SOD) and elevated MDA, NO, and MPO. Mitochondrial bioenergetic enzymes and respiratory complexes were significantly suppressed, suggesting impaired bioenergetics. Histological analysis revealed progressive glomerular atrophy, tubular degeneration, and interstitial inflammation. Electrolyte imbalance (hyponatremia, hypochloremia, hyperkalemia) further confirmed disrupted ion homeostasis. Exposure to PE-MPs induces dose-dependent renal injury through oxidative stress, mitochondrial dysfunction, and impaired renal function. These findings highlight the kidney as a critical target of microplastic toxicity and underscore the need for regulatory attention to environmental microplastic exposure.